Exploring the Therapeutic Potentials of Nonpharmacological Blessing Energy Intervention for the Benefits of Psycho-Mental Impaired Individuals: A Clinical Trial - Dahryn Trivedi; Mahendra Kumar Trivedi; Alice Branton; Sambhu Mondal; Snehasis Jana (Integrative Medicine Reports)
Background: In traditional healing systems, life-force energy or subtle human energy fields have been recognized for millennia. Parallel to conventional therapy, its popularity has grown tremendously in recent years. Due to limited scientific research on biofield therapies, the authors investigated the potential impact of distant biofield/blessing energy interventions on individuals with psychological impairments via virtual methods. Methods: A total of 119 participants (56 male, 63 female) with one or more psycho-mental symptoms were enrolled in these randomized, placebo-controlled, double-blind clinical trials. Two remote biofield/blessing energy interventions, each lasting approximately 5 min, were delivered to 38 subjects in the biofield intervention group on days 0 and 90. Subjects were assessed using standardized psychological questionnaires, which employed a validated scoring scale, as well as safety parameters. Results: Participants in the biofield (blessing) intervention group reported significantly lower levels of perceived psychological symptoms (fatigue, sleep disturbances, stress, cognitive impairment, and emotional distress) compared with both naive and sham control groups (p < 0.0001). Biofield intervention was safe and well-tolerated in all three groups. Conclusion: Distant biofield/blessing energy healing sessions were found to significantly improve psychological and mental health, enhance overall well-being, and pose no safety risks. Therefore, further research is needed to identify key variables for a larger scale intervention study on health outcomes and underlying mechanisms. Trial registration: Clinical Trials Registry Number—India (CTRI/2022/07/043633).